Discovery of Small Anti‐ACE2 Peptides to Inhibit SARS‐CoV‐2 Infectivity (Adv. Therap. 7/2021). Issue 7 (20th July 2021) - Adhikary, Pratik; Kandel, Sashi; Mamani, Umar‐Farouk; Mustafa, Bahaa; Hao, Siyuan; Qiu, Jianming; Fetse, John; Liu, Yanli; Ibrahim, Nurudeen Mohammed; Li, Yongren; Lin, Chien‐Yu; Omoscharka, Evanthia; et al.
Abstract : SARS‐CoV‐2 infects human cells by binding its spike protein to the human ACE2 receptor. Using a peptide biopanning strategy, the authors have discovered small anti‐ACE2 peptides that can effectively block the SARS‐CoV‐2/ACE2 interaction. The anti‐ACE2 peptides can be potentially used as prophylactic or therapeutic agents for SARS‐CoV‐2 and other ACE2‐mediated viruses. This is reported by Kun Cheng and co‐workers in article number 2100087 .